2019
DOI: 10.1021/acs.nanolett.9b02865
|View full text |Cite
|
Sign up to set email alerts
|

Near-Infrared Imaging of Serotonin Release from Cells with Fluorescent Nanosensors

Abstract: Serotonin is an important neurotransmitter involved in various functions of the nervous, blood, and immune system. In general, detection of small biomolecules such as serotonin in real time with high spatial and temporal resolution remains challenging with conventional sensors and methods. In this work, we designed a near-infrared (nIR) fluorescent nanosensor (NIRSer) based on fluorescent singlewalled carbon nanotubes (SWCNTs) to image the release of serotonin from human blood platelets in real time. The nanos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
125
0
16

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 115 publications
(141 citation statements)
references
References 59 publications
0
125
0
16
Order By: Relevance
“…This review provides an overview and a comprehensive survey of the utilization of SWCNTs for biosensing applications. The non-photobleaching, non-blinking fluorescent emission of SWCNTs plays a key role in rendering them optical sensors, enabling in situ, label-free, real-time detection with both spatial and temporal resolution [89,113,115]. Recent studies have demonstrated the detection of proteins using various approaches for surface functionalization, including natural substrates [53,121,125] and synthetic polymers [89,129,145], with the potential to enable long-term continuous monitoring of important biomarkers or to replace costly and time-consuming laboratory testing [173].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This review provides an overview and a comprehensive survey of the utilization of SWCNTs for biosensing applications. The non-photobleaching, non-blinking fluorescent emission of SWCNTs plays a key role in rendering them optical sensors, enabling in situ, label-free, real-time detection with both spatial and temporal resolution [89,113,115]. Recent studies have demonstrated the detection of proteins using various approaches for surface functionalization, including natural substrates [53,121,125] and synthetic polymers [89,129,145], with the potential to enable long-term continuous monitoring of important biomarkers or to replace costly and time-consuming laboratory testing [173].…”
Section: Discussionmentioning
confidence: 99%
“…A recent study has demonstrated the recognition of the neurotransmitter serotonin using SWCNTs wrapped with a serotonin-aptamer. This nanosensor was immobilized on a glass surface, on which human blood platelets were cultured, and were shown to detect serotonin release patterns from the cells in real time [115]. Additionally, DNA-wrapped SWCNTs were utilized for the detection of a single-stranded RNA genome of an intact HIV particle [116] and of doxorubicin, a chemotherapy drug effective against dividing cells due to its affinity to DNA [117].…”
Section: Swcnts As Optical Sensorsmentioning
confidence: 99%
“…11,12,[15][16][17][18]62 For example, recently, a SWCNT-based sensor for another important neurotransmitter (serotonin) has been introduced. 13 Another application is to use SWCNTs as mechanical sensors. In this context, SWCNTs have been used to study movements in cells and the extracellular space in brain tissue.…”
Section: Programmed Release Of Functional Nanosensorsmentioning
confidence: 99%
“…[7][8][9][10] Their surface can be chemically tailored with DNA, peptides, lipids, nanobodies or viruses to sense biologically relevant signaling molecules with high spatiotemporal resolution. [11][12][13][14][15][16][17][18] Thus, such nanomaterials are attractive candidates for biomedical applications. It is also known that nanomaterials such as SWCNTs can be taken up by living cells depending on their size.…”
Section: Introductionmentioning
confidence: 99%
“…More intractably, the UV/Vis light presents poor penetration depth in biological tissues, that is, the PEC sensors worked under UV/Vis light illumination will not work anymore for in vivo detection in the living body due to the lacking of effective light illumination. Inspired from the photothermal therapy strategy for in vivo cancer treatment under near‐infrared (NIR) light irradiation, and NIR fluorescent biosensor for detection of neurotransmitters, we hypothesize that the NIR responsive PEC sensors will be a highly promising option for implementation of un‐biased PEC in vivo detection as the NIR light owns much deeper tissue penetration and better biocompatibility than the UV/Vis light. However, very surprisingly, after carefully searching the reported literatures, the NIR responsive PEC sensors have been rarely reported, and no any practical in vivo PEC detection has been conducted.…”
Section: Background and Originality Contentmentioning
confidence: 99%